The influence of invention - Joss, William Irvin (My University, 1895)
Intoduction: It shall be my purpose in writing this thesis to sum up briefly the services which inventions have rendered to the universe and the influence that the multiplicity of innovations have had upon the moral and social conditions of man. However, I shall not be able to speak of all the great inventions, but will strive to point out some of the earliest and most useful inventions and how these by further improvements have wrought magnificent results. No doubt all who are at all interested in the work of inventions will admit that civilization at its beginning must have been very rude and at the same time very simply.
Citation: Joss, William Irvin. The influence of invention. Senior thesis, Kansas State Agricultural College, 1895.
Morse Department of Special Collections
Keywords: Inventions; Civilization; Social conditions; Man; Theses; Manuscripts (documents)